2016
DOI: 10.1161/atvbaha.115.306834
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Release Niacin/Laropiprant Improves Overall Efficacy of Postprandial Reverse Cholesterol Transport

Abstract: Objectives-Postprandial atherogenic lipoproteins, characterizing high-risk patients, correlate positively with cardiovascular events. Although the effect of niacin on fasting lipids is well established, its impact on atheroprotective reverse cholesterol transport (RCT) pathway and on functional features of circulating lipoproteins during the postprandial state remains indeterminate. Approach and Results-We evaluated RCT pathway during postprandial phase in dyslipidemic patients displaying a low high-density li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Extended-release niacin given immediately before a fat meal suppressed postprandial FFA and plasma TG excursions (53), whereas bedtime dosing failed (54). In addition, patient studies continue to report impairments in insulin sensitivity and/or glycemic control (12)(13)(14)(15)(16)(17) and even increased risk of new-onset diabetes (18). Based on the current results, it seems reasonable to speculate that mealtime dosing might reverse these negative effects on glucose control.…”
Section: A Therapeutically Relevant Niac Exposurementioning
confidence: 83%
“…Extended-release niacin given immediately before a fat meal suppressed postprandial FFA and plasma TG excursions (53), whereas bedtime dosing failed (54). In addition, patient studies continue to report impairments in insulin sensitivity and/or glycemic control (12)(13)(14)(15)(16)(17) and even increased risk of new-onset diabetes (18). Based on the current results, it seems reasonable to speculate that mealtime dosing might reverse these negative effects on glucose control.…”
Section: A Therapeutically Relevant Niac Exposurementioning
confidence: 83%
“…42 Statin alone did not increase HDL particle concentration or macrophage cholesterol efflux capacity, even though it raised HDL-C. 42 In dyslipidemic patients on stable statin therapy, 12 weeks of extended-release niacin/laropiprant therapy reduced CETP activity, moderately improved plasma efflux capacity from macrophages, and increased the ability of HDL particles to deliver CE back to the liver during the postprandial phase. 43 These results suggest that specific subgroups of patients at high cardiovascular risk might benefit from combination therapy of statin and niacin for cardioprotection. However, as the authors pointed out, whether the subtle benefits may translate into improved clinical outcome and whether the benefits were sufficient to overcome the side effects is unclear.…”
Section: Targeting High-density Lipoprotein and Reverse Cholesterol Tmentioning
confidence: 90%
“…However, as the authors pointed out, whether the subtle benefits may translate into improved clinical outcome and whether the benefits were sufficient to overcome the side effects is unclear. 43 The controversy regarding the benefits of niacin combinations with statins on RCT and reducing cardiovascular events in human continues, and further investigation is needed.…”
Section: Targeting High-density Lipoprotein and Reverse Cholesterol Tmentioning
confidence: 99%
“…Thus, studies showed that niacin improved [37, 38] or did not change [39] HDL’s overall efflux capacity without improving ABCA1-specific efflux [37, 38]. Importantly, the improvement in total efflux correlated with the increase in HDL-C [38].…”
Section: Hdl-c–raising Therapies Particle Number Protein Cargo and mentioning
confidence: 99%
“…Niacin reduced ABCA1-dependent efflux after dyslipidemic patients ingested a typical western meal. However, HDL particles isolated from patients receiving niacin displayed an enhanced capacity to deliver cholesteryl esters to hepatic cells, improving overall reverse cholesterol transport [37]. Of note, a secondary analysis of a subset of dyslipidemic patients in the AIM-HIGH trial uncovered a significant reduction in cardiovascular risk [56].…”
Section: Unresolved Issues In Hdl Metabolismmentioning
confidence: 99%